The Role Of Sharia Marketing In Indonesia: A Systematic Literature Review - Deviyanti, Sri; Misbach, Irwan; Siradjuddin, Siradjuddin (Jurnal Ilmiah Ekonomi Islam, 2024)
Indonesia is a predominantly Muslim country, indicating a vast market potential for halal products and services. However, many businesses have yet to fully implement Sharia marketing. This article aims to examine the extent of the role of Sharia marketing in Indonesia. The research method used is a systematic literature review. The literature search was conducted using the Google Scholar database with the assistance of the Publish or Perish 8 application. The search for articles was conducted using the keywords 'Sharia Marketing', 'Sharia Marketing', and 'Islamic Marketing'. A systematic literature review of 27 articles spanning from 2018 to 2023 revealed that Islamic marketing plays an important role in Indonesia. Specifically, it assists in the development of Islamic financial institutions, helps in the development of micro, small, and medium enterprises, and improves the image of educational institutions in Indonesia. The research concludes that implementing Sharia marketing is important for business people.